Optimising road maintenance - Mark O. Harvey (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
Mathematical optimisation models, supported by suitable data, can assist decision making about allocating funds between alternative maintenance tasks and about the size of the maintenance budget. The maintenance optimisation problem is, in essence, to find the optimum balance between the costs and benefits of maintenance, while taking into account various constraints (Dekker 1996). For a given road segment, choices have to be made between alternative treatment types and the times to implement those treatments. Where maintenance funds are limited, there is an additional problem of balancing the competing needs of the different segments. Maintenance tends to be underfunded relative to investment because the smaller, less obvious nature of maintenance works relative to new infrastructure (Semmens 2006, Zeitlow 2006). But deferring maintenance in the short term can be expensive in the long term, a point that can be brought to the attention of decision makers by quantifying the costs of underfunding maintenance.
Keywords: 330